A cucurbituril–pillararene ring-on-ring complex. Issue 53 (11th June 2021) - Zhang, Dejun; Tang, Hao; Zhang, Guozhen; Wang, Lingyun; Cao, Derong
Abstract : A water-soluble ring-on-ring complex was formed by the portal binding between a perfunctionalized polycationic pillar[5]arene (TPT[5]) and a cucur-bit[10]uril (CB[10]). Different binding behaviours were observed for different guests. Abstract : A new type of non-intertwined ring-on-ring assembly was formed by the portal binding between a perfunctionalized polycationic pillar[5]arene and a cucurbit[10]uril, demonstrating a facile approach to solubilize a large macrocycle in water. Different binding behaviors towards guests were observed for the high-order complex, enriching the functional supramolecular systems.